Therapeutic effect of Ipomoea Batatas extracts on induced psoriasis in mice - Anuar Sani; Wan Omar Abdullah; Mohamed Adel Rahim; Ngah Zasmy Unyah; Nur Syahrina Rahim; Sazlina Kamaralzaman (College of Pathologists, Academy of Medicine Malaysia, 2024)
The 2015 Annual Scientific Meeting of the College of Pathologists, Academy of Medicine Malaysia & 40th Anniversary Celebration of the Pathology Advocates was held at Berjaya Time Square Hotel, Kuala Lumpur from 13-14 June 2015.